Risk of chemotherapy-induced amenorrhea in patients with breast cancer: a systematic review and meta-analysis. (2nd June 2016) - Zavos, A.; Valachis, A.
Abstract: Background : The aim of the study was to calculate the rate of chemotherapy-induced amenorrhea (CIA) after treatment with different adjuvant therapies in patients with breast cancer and to evaluate the risk factors for CIA based on the quality of evidence. Patient and methods : A search of PubMed and ISI Web of Science was performed. All published trials with female breast cancer patients who received adjuvant chemotherapy and presented data on the rate of CIA were considered eligible. The pooled rates of CIA were calculated by random effects model. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated for each potential risk factor for CIA by using the generic inverse weighted method. Results : We identified 580 potentially relevant studies, of which 75 were included in the analysis. Among 75 eligible studies, 19 different definitions of CIA have been used. The pooled rate of CIA was 55% (95% CI 50–60%) including 23 673 patients from 74 studies. The rate of CIA was increased by age with an estimate of 26% (95% CI 12–43%), 39% (95% CI 31–58%), and 77% (95% CI 71–83%) for women <35, 35–40, and >40 years old, respectively. Two risk factors were associated with the occurrence of CIA and were supported by strong level of evidence: older age (>40 years old), and the use of tamoxifen. Conclusions : This meta-analysis summarized the updated evidence on the impact of different adjuvant treatment regimens for breast cancer in menstruation and could serve as a helpful guide for oncologists during the discussion with their patients on fertility issues before decision on adjuvant therapy is made. A uniform definition of CIA is essential in future studies to make the interpretation of results more reliable.